Pengembangan Sistem Pendukung Keputusan Menggunakan Metode Tsukamoto - Graha Prakarsa; Vani Maharani Nasution (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Hanger maintenance process this time based on the circulation from hanger give to the production side. No standard calculation, looking for risk percentage for hanger go into maintenance, become a problem. The hanger must have a standard calculation for percentage value, where the value can provide a clear decision. There is a method in Fuzzy Logic, that the Tsukamoto method, can be utilized in making a decision. This research is based on the problem of how to make a standard calculation, to looking for the risk percentage level for hanger go into maintenance, by applying Fuzzy Logic Tsukamoto method, so that the calculation becomes faster, accurate, and precise. The result from the application of the Tsukamoto method, to find the risk percentage level for hanger enter maintenance, for example at hanger Back Caesar, the resulting level of percentage hanger requirement is 91%, and hanger maintenance risk level 70,375%. The final result shows hanger Back Caesar has a high maintenance risk level (range between 54,6-100%) and well plan maintenance action. Application of Tsukamoto method that has been done shows that to find the risk level percentage for hanger go into maintenance, the first must be looking for output crisp from the percentage level of hanger that needed with the Tsukamoto method.